(untitled) (Scientia Agricola, 2016)
In recent years, the use of biostimulants in sustainable agriculture has been growing. Biostimulants can be obtained from different organic materials and include humic substances (HS), complex organic materials, beneficial chemical elements, peptides and amino acids, inorganic salts, seaweed extracts, chitin and chitosan derivatives, antitranspirants, amino acids and other N-containing substances. The application of biostimulants to plants leads to higher content of nutrients in their tissue and positive metabolic changes. For these reasons, the development of new biostimulants has become a focus of scientific interest. Among their different functions, biostimulants influence plant growth and nitrogen metabolism, especially because of their content in hormones and other signalling molecules. A significant increase in root hair length and density is often observed in plants treated with biostimulants, suggesting that these substances induce a “nutrient acquisition response” that favors nutrient uptake in plants via an increase in the absorptive surface area. Furthermore, biostimulants positively influence the activity and gene expression of enzymes functioning in the primary and secondary plant metabolism. This article reviews the current literature on two main classes of biostimulants: humic substances and protein-based biostimulants. The characteristic of these biostimulants and their effects on plants are thoroughly described.